ANALISIS PENGARUH KUALITAS PELAYANAN DAN ASPEK-ASPEK TRANSAKSIONAL TERHADAP LOYALITAS PELANGGAN PADA SEKTOR PERBANKAN RITEL (STUDI PADA PARA PEDAGANG KECIL DI PASAR BOJONG INDAH JAKARTA SEBAGAI NASABAH PERBANKAN RITEL) - Christina Ariadne Sekar Sari (Universitas Mercu Buana, 2015)
This study aimed to know the influence of the quality of service and transactional aspects on loyalty of merchants at the market of Bojong Indah, West Jakarta, as the customer of government’s bank in retail banking sector. This study uses the five aspects of service quality which is called SERVQUAL together with transactional aspects. The results of this study indicate the aspects of service quality that can build long-term relationships with customers, have the lower score than aspects of transactional. Multiple linear regression analysis results showed that simultaneously, 22.7% of the variance of Y (customer loyalty) can be explained by changes in all variables the quality of service that is tangible, reliability, responsiveness, assurance, empathy, and transactional. While 77.3% the rest is explained by other factors outside the model. Partially, of the six independent variables only quality reliability, empathy, and transactional that have significant influence on customer loyalty. Keywords: Service quality, transactional, customer loyalty.